Fatherhood and Managerial Style - Dahl, Michael S.; Dezső, Cristian L.; Ross, David Gaddis (Administrative Science Quarterly, 2012)
Motivated by a growing literature in the social sciences suggesting that the transition to fatherhood has a profound effect on men’s values, we study how the wages of employees change after a male chief executive officer (CEO) has children, using comprehensive panel data on the employees, CEOs, and families of CEOs in all but the smallest Danish firms between 1996 and 2006. We find that (a) a male CEO generally pays his employees less generously after fathering a child, (b) the birth of a daughter has a less negative influence on wages than does the birth of a son and has a positive influence if the daughter is the CEO’s first, and (c) the wages of female employees are less adversely affected than are those of male employees and positively affected by the CEO’s first child of either gender. We also find that male CEOs pay themselves more after fathering a child, especially after fathering a son. These results are consistent with a desire by the CEO to husband more resources for his family after fathering a child and the psychological priming of the CEO’s generosity after the birth of his first daughter and specifically toward women after the birth of his first child of either gender.